2019
DOI: 10.1111/nep.13682
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dialysate Ca concentrations on the therapeutic effects of etelcalcetide with concomitant drugs in patients with secondary hyperparathyroidism

Abstract: Aim Secondary hyperparathyroidism (SHPT), a complication of haemodialysis, is commonly treated with calcimimetics. The impact of dialysates containing different calcium (Ca) concentrations on clinical efficacy of calcimimetics are unclear. We examined whether dialysate Ca concentrations influence the efficacy and dosing of etelcalcetide with concomitant drugs. Methods We performed post hoc analyses of a 52‐week, open‐label, multicentre study of etelcalcetide in Japanese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…As in the prior 52-week study [ 17 ], we found no differences in the efficacy and safety of etelcalcetide when patients were divided into subgroups according to their dialysate Ca concentration (Tables 3 and 5 ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As in the prior 52-week study [ 17 ], we found no differences in the efficacy and safety of etelcalcetide when patients were divided into subgroups according to their dialysate Ca concentration (Tables 3 and 5 ).…”
Section: Discussionsupporting
confidence: 71%
“…2), which might reflect a relationship between younger age and greater parathyroid gland sensitivity/PTH secretory potential [13][14][15][16], although this has yet to be confirmed in the context of SHPT. As in the prior 52-week study [17], we found no differences in the efficacy and safety of etelcalcetide when patients were divided into subgroups according to their dialysate Ca concentration (Tables 3 and 5).…”
Section: Discussionsupporting
confidence: 70%
“…Most of the dialysis units followed the JSDT guideline published in 2008 [ 25 ] and updated in 2013 accordingly [ 26 ]. Both cinacalcet and evocalcet are effective for controlling secondary hyperparathyroidism [ 27 ] irrespective of D-Ca [ 28 , 29 ]. By comparing the effects on serum calcification propensity (T50), a surrogate marker of calcification, Shoji T et al reported that a calcimimetic agent etelcalcetide was more effective than a vitamin D receptor activator maxacalcitol [ 30 ].…”
Section: Discussionmentioning
confidence: 99%